Self-directed learning with knowledge management model on academic achievement and digital literacy abilities for employees of a Thai energy organization - Silamut, Aime acha; Sovajassatakul, Thanongsak (My University, 2021)
Previously, we described a self-directed learning with knowledge management (SDL-KM) model (Silamut and Petsangsri 2020), to motivate learners in an organization to learn from internal-and-external knowledge management resources to enhance their Academic Achievement and Digital Literacy Abilities. In this paper, we aimed to demonstrate the value of this model by comparing these abilities in a controlled experiment with employees of an energy regulatory organization in Bangkok, Thailand. 40 employees were randomly selected, using stratified sampling, and divided into an experimental group (20) and control group (20), who participated in learning activities on two energy topics. The research instruments were data collection at the end of the lessons, which included information on Academic Achievement and Digital Literacy Ability assessment. Means, standard deviations and one-way MANOVA statistics were computed. As the results, the experimental group had higher Digital Literacy Abilities than the control group (p < 0.05), but there was no significant difference between the groups for Academic Achievement. SDL-KM model encourages learners to learn by themselves, knowing how to use Digital Literacy Abilities to support KM. This will lead to success in their work.
Keywords: Academic achievement; Digital literacy abilities; Knowledge management; Self-directed learning